Tissue-specific protective properties of lithium: comparison of rat kidney, erythrocytes and brain - Roubalová, Lenka; Vošahlíková, Miroslava; Slaninová, Jiřina; Kaufman, Jonáš; Alda, Martin; Svoboda, Petr (Naunyn-Schmiedeberg's archives of pharmacology, 2021)
Lithium (Li) represents a first choice mood stabilizer for bipolar disorder (BD). Despite extensive clinical use, questions regarding its mechanism of action and pathological mechanism of renal function impairment by Li remain open. The present study aimed to improve our knowledge in this area paying special attention to the relationship between the length of Li action, lipid peroxidation (LP), and Na+/K+-ATPase properties. The effects of therapeutic Li doses, administered daily to male Wistar rats for 1 (acute), 7 (short term) and 28 days (chronic), were studied. For this purpose, Na+/K+-ATPase activity measurements, [3H]ouabain binding and immunoblot analysis of α-Na+/K+-ATPase were performed. Li-induced LP was evaluated by determining the malondialdehyde concentration by HPLC. Sleep deprivation (SD) was used as an experimental approach to model the manic phase of BD. Results obtained from the kidney were compared to those obtained from erythrocytes and different brain regions in the same tested animals. Whereas treatment with therapeutic Li concentration did not bring any LP damage nor significant changes of Na+/K+-ATPase expression and [3H]ouabain binding in the kidney, it conferred strong protection against this type of damage in the forebrain cortex. Importantly, the observed changes in erythrocytes indicated changes in forebrain cortices. Thus, different resistance to SD-induced changes of LP and Na+/K+-ATPase was detected in the kidney, erythrocytes and the brain of Li-treated rats. Our study revealed the tissue-specific protective properties of Li against LP and Na+/K+-ATPase regulation.
Keywords: modely nemocí na zvířatech; sodíko-draslíková ATPasa; Sleep Deprivation; Male; Rats, Wistar; Lithium Carbonate; spánková deprivace; Brain; Antimanic Agents; Kidney; mužské pohlaví; potkani Wistar; Lithium; Rat tissues; lithiumkarbonát; Malondialdehyde; antimanika; krysa rodu Rattus; Time Factors; Na+/K+-ATPase; Animals; Sodium-Potassium-Exchanging ATPase; ledviny; zvířata; Rats; časové faktory; Disease Models, Animal; mozek; erytrocyty; peroxidace lipidů; Erythrocytes; Sleep deprivation; Lipid Peroxidation; bipolární porucha; Bipolar Disorder